منهج التفسير اللغوي في تفسير الكشاف للزمخشريLinguistic Interpretation Methodology in Tafsīr al-Kashshāf by al-Zamakhsharī (Al-Qamar, 2021)
The interest in the interpretation and study of the Qur’anic text opened the appetite for the commentators, so I ask the saliva of their pens, and open their hearts until they donated treasures and pearls, which were represented in the huge explanatory legacy that the Qur’anic library abounds in. Those curricula are well-known to scholars of interpretation, the linguistic approach. In this particular context - through the book of interpretation of the Scouts - we will content ourselves with studying the most basic aspects of the linguistic approach that Al-Zamakhshari took in his Scouts. I try to present this research according to the following methodology: Introduction, a brief translation of Al-Zamakhshari, the definition of Tafsir Al-Kashshaf, the definition of linguistic interpretation, the emergence of linguistic interpretation, the status of linguistic interpretation, features of linguistic interpretation of Al-Zamakhshari.
Keywords: Linguistic Interpretation; Methodology; Kashshāf, al-Zamakhsharī